METODE MENUMBUHKEMBANGKAN KECERDASAN EMOSIONAL DAN SPIRITUAL TERHADAP ANAK - Razali, Muslim (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
Emotional and spiritual intelligence helps a person to find meaning in life and happiness. Successful people are not only sufficient with intellectual intelligence but need emotional intelligence to feel happy about their success. In addition, spiritual intelligence is also needed to feel pious and serve sincerely. Intellectual intelligence is apparently not enough to guarantee decision making, so today people are starting to talk about other intelligences, namely emotional intelligence and spiritual intelligence